Ocular extraintestinal manifestations and treatments in patients with inflammatory bowel disease - Rodriguez Duran, Mariana; O’Keefe, Ghazala A. Datoo (Frontiers in Ophthalmology, 2024)
Between 3-47% of patients with inflammatory bowel disease (IBD) have extraintestinal manifestations (EIMs), and between 1.3-86.9% of patients with IBD suffer from ocular EIMs (O-EIMs) making the eye the third most common organ affected. These O-EIMs exist among a spectrum, with a variety of types and amounts of inflammation which can lead to decreased vision, and in some cases, vision loss, without treatment.We performed a literature review concerning O-EIMs in patients who had or were later found to have a diagnosis of IBD in order to identify ocular EIMs that commonly occur with IBD and to assess which patients with IBD may be at higher risk of developing O-EIMs. We were also interested in ascertaining whether O-EIMs were more common in specific populations of people or in specific subtypes of IBD. Lastly, we explored the common treatments of O-EIMs in patients with IBD.Upon review of the literature, we found that the most common O-EIMs are episcleritis and uveitis. Anterior uveitis is more commonly seen, although, inflammation may occur in the posterior segment of the eye as well and may also manifest as retinal vasculitis. While these diagnoses are sometimes known retrospectively, most patients present with nonspecific eye complaints of which decreased vision with or without pain is the most common.Visual symptoms associated with ocular EIMs may be non-specific so physicians should have a low threshold to refer to ophthalmology for visual complaints. It is important to keep in mind that ocular EIMs can cluster with skin and joint EIMs. Screening should be prioritized for female patients with Crohn's disease and concurrent arthritis. Treatments for O-EIMs are outlined and compared in this paper as well.